Technology Foresight: International Experience - Michael Keenan (Foresight and STI Governance)
To coincide with the recent official publication of the results of the Russian Technology Foresight Programme, this paper provides a brief overview of international experiences in national technology foresight. The author demonstrates the foresight practice growing popularity both on the international level and within certain states, describes different rationales that justify the use of foresight, highlighting their shift away from an original R&D priority-setting focus towards a more process-oriented focus that emphasises dialogue and networking between different actors in national systems of innovation. The methodological approaches used in different countries are compared, suggesting a possible link between method preferences and political and institutional cultures. Factors are also considered that complicate the evaluation of foresight researches, and perspectives of their further development are briefly analyzed.